P175 ELECTROCARDIOGRAPHIC ELEMENTS ASSOCIATED WITH ARRHYTHMIC RISK IN BRUGADA SYNDROME. (18th May 2022) - Berloni, M; Di Domenico, A; De Carolis, B; Canovi, L; Vitali, F; Bertini, M; Guardigli, G; Balla, C
Abstract: Introduction: Brugada syndrome is an inherited disease characterized by an increased arrhythmic risk and sudden death. The type 1 ECG pattern is the only standard required to make a diagnosis but the stratification of arrhythmic risk remains a controversial element. Some electrocardiographic signs have been described as associated with an increased arrhythmic risk. We present a case of Brugada Syndrome in which different electrocardiographic elements of incremental risk could have predicted the later evolution of the clinical case. Clinical Case: A 68–year–old male patient with family history of sudden cardiac death (brother 51aa) and occasional finding of Brugada type 1 ECG pattern (2009), implanted with Medtronic bicameral ICD device in primary prevention. The electrocardiogram shows type 1 Brugada pattern in the right precordials with characteristic ST–elevation, followed by a concave ST segment, one of the signs of association with an increased arrhythmic risk; first–degree AV block with a long PR (323 msec) associated with the presence of the SCN5A mutation and an increased risk of arrhythmic events and sudden cardiac death; in the end a fragmented QRS in V2 with extended duration (153 ms). At the next follow–up the patient had some episodes of arrhythmic storm, effectively treated by the device; in consideration of the arrhythmic burden, he was subjected to epicardial ablation and was also subjected to genetic analysis that was positive for pathological mutation on the SCN5A gene (SCN5A ex 22: c.3929C>T;p.Pro1310Leu). Conclusions: Brugada Syndrome can be diagnosed from the type 1 ECG pattern, but the current risk stratification score remains a controversial element. Electrocardiographic signs of malignancy can contribute to create a multiparametric evaluation of the patient in order to predict future arrhythmic events. Fig 1 . ECG: RS 74 bpm, first–degree AV block (PR 323 msec), BFA, Brugada type 1 pattern (QRS 153 ms), fragmented QRS in V2. Fig. 2 Family tree.